Plan de Desarrollo Turistico Sostenible para Mejorar la Gestión Turistica del Cantón Guamote-Provincia de Chimborazo. - Jara Córdova, Vanesa Margarita (2013)
Tourism in recent years has become one of the most important activities in the world, therefore, the research problem, has been aimed at analyzing some needs of this sector, specifically in Guamote Canton , Chimborazo Province , because even though this place has many tourist attractions, it has had insufficient attention by the Guamote Municipality and the Ecuador Tourism Ministry , hence , the overall objective is to make sustainable tourism development plan in order to convert this place into a national and international tourist destination. The sustainable tourism development plan for the Canton Guamote, has the following objectives as: Realizing scientifically based theoretical foundation of the tourism sector, we conducted a demand analysis by market research; and also conducted a strategic review in which it was possible to analyze the internal and external situation of the canton, achieving determine the strengths, weaknesses, opportunities and threats thus developed the SWOT matrix, and then define the business philosophy through the mission, vision, objectives, policies and strategies conducive to the proper management of the tourist attractions.